Transcendental Phenomenology in the Context of Organitational Studies - Sánchez Manchola, Iván Darío; Losada Otálora, Mauricio (Cuadernos de Administración, 2009)
In the present paper the authors analyze the contribution that the transcendental phenomenology approach (concretely the ideas developed by Husserl) has made to the organizational studies. The article is divided into three parts. The first one presents a synopsis of the phenomenological approach as the basis for the development of a philosophical project that transcends the positivist conception of scientific knowledge. The second part analyzes phenomenology within the broad context of social studies and especially within the context of organizational studies, pointing out how, in the light of the ideas developed by Burrel and Morgan (1979), the phenomenological approach is inscribed and contributes to the development of the interpretive point of view. The third one presents the author’s concluding remarks